1992
DOI: 10.1063/1.106620
|View full text |Cite
|
Sign up to set email alerts
|

Role of substrate temperature in molecular-beam epitaxial growth of high-power GaAs/AlGaAs lasers

Abstract: Articles you may be interested inReliable substrate temperature measurements for high temperature AlGaAs molecularbeam epitaxy growth J. Vac. Sci. Technol. B 13, 290 (1995); 10.1116/1.588367 Highpower fundamental mode AlGaAs quantum well channeled substrate laser grown by molecular beam epitaxy Appl. Phys. Lett. 55, 1059 (1989); 10.1063/1.101704 Highpower (2.2 W) cw operation of (111)oriented GaAs/AlGaAs singlequantumwell lasers prepared by molecularbeam epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…An optimized growth strategy incorporates high temperature up to the quantum well layer preventing oxygen from getting incorporated, followed by a relatively low temperature growth of the top cladding layer, which ensures a smooth surface morphology and uniform material composition [7,8]. Uniformity of the top cladding layer is more important than that of the lower cladding layer as all of the etching and patterning processes are carried out on the top cladding layer.…”
Section: Asymmetrical Waveguidementioning
confidence: 99%
“…An optimized growth strategy incorporates high temperature up to the quantum well layer preventing oxygen from getting incorporated, followed by a relatively low temperature growth of the top cladding layer, which ensures a smooth surface morphology and uniform material composition [7,8]. Uniformity of the top cladding layer is more important than that of the lower cladding layer as all of the etching and patterning processes are carried out on the top cladding layer.…”
Section: Asymmetrical Waveguidementioning
confidence: 99%
“…Below 700°C, oxygen is incorporated into AlGaAs with unity sticking coefficient and is found to accumulate at AlGaAs/GaAs interfaces. 30,31 Once incorporated in AlGaAs, oxygen acts as an efficient nonradiative recombination center. 32,33 If located in the active layers of a light emitter or at the interfaces to the active layer, nonradiative recombination centers dramatically reduce the efficiency of the device.…”
Section: Eoe Integration Processmentioning
confidence: 99%
“…The authors of both quoted papers [1,2] also showed that QW photoluminescence (PL) intensities were in excellent correlation with Jth when growth temperature was changed and the quality of the AlGaAs cladding layer played a more decisive role than the active layer quality. Contrary to that Weisbuch et al [3] reported that the quality of QW was more Sensitive to the growth temperature than the AlGaAs cladding layer.…”
mentioning
confidence: 99%
“…De, 85.60.Jb, 73.20.Dx In the case of AlGaAs/GaAs GRIN SCH SQW lasers it has been found that the threshold current density, Jth, is critically dependent on growth parameters and shows W-shape dependence on the substrate temperature with minima at 375°C and 650°C [1] or at 740°C and 820°C according to other source [2]. The authors of both quoted papers [1,2] also showed that QW photoluminescence (PL) intensities were in excellent correlation with Jth when growth temperature was changed and the quality of the AlGaAs cladding layer played a more decisive role than the active layer quality.…”
mentioning
confidence: 99%